Hemodialysis Adequacy Monitoring Information System: Minimum Data Set and Capabilities Required - Jebraeily, Mohamad (Acta Inform Med, 2015)
INTRODUCTION: In dialysis centers both nephrologists and nurses are faced with the challenge of ensuring reliable and efficient care accordance with the clinical guideline. Hemodialysis adequacy monitoring information system therefore enable the automation of tasks, which ultimately allows doctors and nursing staff more time to dedicate to the individual treatment of patients. Development of the information systems in healthcare has made the use of the Minimum data set inevitable. The purpose of this study was determined MDS and capabilities required in hemodialysis adequacy monitoring information system. METHOD AND MATERIALS: This is a cross-sectional survey conducted with participation of 320 nephrology specialists in 2015. Data were collected using an electronic questionnaire which was estimated as both reliable and valid. The data were analyzed by SPSS software descriptive statistics and analytical statistics. RESULTS: Overall 42 data elements were determined as final set in 4 major categories (patient demographics, medical history, treatment plan and hemodialysis adequacy). The most capabilities required of hemodialysis information system were related to calculate of dialysis adequacy Index (4.80), advice optimal dose of dialysis for each patient (4.63), Easy access to information system without restrictions of time and place (4.61), providing alerts when dialysis adequacy index below the standard (4.55) and Interchange to other information systems in hospitals (4.46) respectively. CONCLUSION: In design and implementation of information systems focus on MDS and identification IS capabilities based on the users’ needs, due to the wide participation users and also the success of the information system. Therefore it is necessary that MDS evaluated carefully with regard to the intended uses of the data. Also information systems based on capabilities the ability to meet the needs of their users.